2024
DOI: 10.3389/fvets.2024.1303096
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance of paratuberculosis in Alpine-dwelling red deer (Cervus elaphus)

Anita Filippi,
Chiara Garbarino,
Matteo Nava
et al.

Abstract: Paratuberculosis (Johne’s disease) is a globally widespread infectious disease affecting domestic and wild ruminants, caused by Mycobacterium avium subsp. paratuberculosis (MAP). The bacterium is excreted in the feces and is characterized by high environmental resistance. The new Animal Health Law (Regulation EU 2016/429) on transmissible animal diseases, recently in force throughout the European Union, includes paratuberculosis within the diseases requiring surveillance in the EU, listing some domestic and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It appears that a low seroprevalence of MAP in wild ruminants is not uncommon in Europe. Tavernier et al ( 10 ) reported a prevalence of 4.1% in the Belgian roe deer population, while a recent Italian study found a similarly low overall seroprevalence of 5.9% in red deer using different diagnostic tools ( 62 ). In addition, Machackova et al ( 63 ) found no significant difference in the seroprevalence reported for MAP (5.3%) between farmed and wild red deer.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that a low seroprevalence of MAP in wild ruminants is not uncommon in Europe. Tavernier et al ( 10 ) reported a prevalence of 4.1% in the Belgian roe deer population, while a recent Italian study found a similarly low overall seroprevalence of 5.9% in red deer using different diagnostic tools ( 62 ). In addition, Machackova et al ( 63 ) found no significant difference in the seroprevalence reported for MAP (5.3%) between farmed and wild red deer.…”
Section: Discussionmentioning
confidence: 99%